Tinjauan Yuridis Penguatan Cagar Budaya pada Daerah Istimewa Yogyakarta - Putri, Octavia Aresia; Zahro, Maulidatuz; Sholikhah, Mar’Atus; Rahayu, Puji; Marom, Nailul; Riswantoro, Ganaudi; Hapsari, Dwi Ratna Indri (Lex Journal: Kajian Hukum & Keadilan, 2023)
This study aims to analyze the juridical perspective on the cultural heritage protection regulation in Indonesia, particularly in the Special Region of Yogyakarta (DIY). Employing a case study approach, this research explores the implementation of the Cultural Heritage Law in the context of DIY, as well as the efforts of the Yogyakarta Regional Government to strengthen and preserve cultural heritage amidst social polarization. The study also addresses challenges faced in preservation endeavors, such as limited resources and sustainable maintenance efforts. By analyzing juridical aspects and field practices, this research provides a richer understanding of the execution of the Cultural Heritage Law in DIY. Through community participation, DIY effectively manages to safeguard cultural heritage despite differences and societal polarization. The study yields an in-depth insight into the pivotal role of the Cultural Heritage Law and the efforts of the DIY Government in conserving cultural richness for future generations.